Aktivitas Antioksidan dan Evaluasi Fisik Sediaan Krim Tabir Surya dari Bubur Rumput Laut Turbinaria conoides dan Serbuk Daun Kelor (Moringa oleifera) - Rini Yanuarti; Dede Komarudin; Ginanjar Pratama (Jurnal FishtecH, 2021)
Moringa and brown seaweed (T. conoides) are known as natural ingredients that are good for the human body. One of them was a good bioactive component as a cosmetic. Research on the combination of these two ingredients has never been done. The aims of this study were to determine the best sunscreen cream from the combination of Moringa leaves and T conoides. In this study, several stages were carried out, namely the production of seaweed porridge and Moringa leaf powder,  and formulation of cream preparations with the ratio treatment of T. conoides. and Moringa, namely 1:1 (S), 1:2 (T), 2:1 (U) and control/without treatment (R). The tests included antioxidant and evaluation of physical parameters of sunscreen cream preparations. Evaluation of physical parameters included centrifugal test, emulsion type, globule diameter, and organoleptic. Antioxidant activity test showed that cream S was significantly different (p<0.005) from cream T and cream U, and it was strong antioxidant activity. The centrifugal test for all treatments showed that all cream preparations were stable because there was no phase separation. The type of emulsion in all treatments was O/W. The diameter of the globules in all treatments had sizes that were still within the allowable range. The organoleptic results on the color and aroma parameters of each cream were not significantly different (p<0.005) in all treatments. These results are different from the appearance parameters because cream S and T are significantly different (p<0.005). Cream S is the best cream in this study from the antioxidant activity and all evaluation parameters.